Situational analysis of human and agricultural health practice: One Health and antibiotic use in an indigenous village in rural Punjab, India - Jarnail Singh Thakur; Anjali Rana; Rajbir Kaur; Ronika Paika; Srikanth Konreddy; Mary Wiktorowicz (One Health)
Antimicrobial resistance (AMR) represents one of the biggest threats to health globally. The rise of AMR has been largely attributed to the misuse and abuse of antimicrobials in veterinary, human, and agricultural medicine. This study aimed to assess human, livestock, and agricultural health profiles, and practices of One Health and antibiotic use through a situational analysis of an Indigenous village Gurah, in a rural area of Mohali district in Punjab state using a demographic and facility survey. A survey questionnaire was used to collect information on the village's socio-demographic, human, livestock, and agricultural profiles. The study included 77 households from the village Gurah, with the majority i.e., 71.4 % engaged in agricultural activity and 68.8 % with livestock. Survey results showed that self-reported adherence to any medicine prescribed by doctors was high (92.3 %) and self-medication reported by the respondents was 11 %. Forty-two percent of antibiotic consumption was verified from prescription. The major crops grown in the village were exposed to pesticides, and most dairy and non-dairy products were sold in markets, with consumers unaware of any pesticide or antibiotic exposure. Additionally, villagers were unaware of disease diagnosis and the medicines their livestock consumed. Findings from veterinarians revealed that around 50 % of the livestock was given antibiotics for treatment for mastitis. In our study, 67.9 % of the green fodder for animals was homegrown and pesticide use was reported. The study reported that 81.1 % of the animal feed additives were purchased from the market and farmers might be unaware whether commercially-purchased feed contains antibiotics. The results provide a picture of the current situation and guide further research for the containment of AMR under the One Health approach. Inadequate multi-sectoral and cross-disciplinary efforts to combating AMR in current practice call for prompt coordinated action integral to a “One Health approach.”